logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
0 votes

$\lim\limits_{h\to 0}\large\frac{f(2h+2+h^2)-f(2)}{f(h-h^2+1)-f(1)}$ given that $f'(2)=6$ and $f'(1)=4$

$\begin{array}{1 1}(a)\;does\;not\;exist&(b)\;is\;equal\;to\;-3/2\\(c)\;is\;equal\;to\;3/2&(d)\;is\;equal\;to\;3\end{array}$

Can you answer this question?
 
 

1 Answer

0 votes
$\lim\limits_{h\to 0}\large\frac{f(2h+2+h^2)-f(2)}{f(h-h^2+1)-f(1)}$
$\Rightarrow \lim\limits_{h\to 0}\large\frac{f'(2h+2+h^2)(2+2h)}{f'(h-h^2+1)(1-2h)}$
$\Rightarrow \large\frac{6\times 2}{4\times 1}$
$\Rightarrow \large\frac{3}{2}$
Hence (c) is the correct answer.
answered Dec 30, 2013 by sreemathi.v
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...